2020
DOI: 10.1128/jb.00692-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Differences between Listeria monocytogenes EGDe Isolates Reveal Crucial Roles for SigB and Wall Rhamnosylation in Biofilm Formation

Abstract: Listeria monocytogenes is a Gram-positive firmicute that causes foodborne infections, in part due to its ability to use multiple strategies, including biofilm formation, to survive adverse growth conditions. As a potential way to screen for genes required for biofilm formation, we harnessed the ability of bacteria to accumulate mutations in the genome over time, diverging the properties of seemingly identical strains. By sequencing the genomes of four laboratory reference strains of the commonly used L. monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…Surface-adhered L. monocytogenes was determined to be 1.3 ± 0.2 μm by 0.6 ± 0.07 μm ( Fig. 1F , arrows) and modest extracellular polysaccharide (EPS) secretion was evident, as described previously ( 53 56 ). Surface adhered Exophiala spp.…”
Section: Resultssupporting
confidence: 78%
“…Surface-adhered L. monocytogenes was determined to be 1.3 ± 0.2 μm by 0.6 ± 0.07 μm ( Fig. 1F , arrows) and modest extracellular polysaccharide (EPS) secretion was evident, as described previously ( 53 56 ). Surface adhered Exophiala spp.…”
Section: Resultssupporting
confidence: 78%
“…The data presented here suggest an explanation for the common detection of mutations in the sigB operon of L. monocytogenes (28,(33)(34)(35)(36)55), including an earlier study in our own laboratory where an rsbV missense mutation arose during routine subculture (31).…”
Section: Emergence Of Mutated Alleles Within the Sigb Operonmentioning
confidence: 53%
“…It has been proposed that the signal transduction cascade in L. monocytogenes can be inferred from the well-studied B. subtilis , since both species share a high level of conservation ( Ferreira et al, 2004 ). Many studies of σ B regulation in L. monocytogenes have confirmed that the signal transduction pathways likely function in a very similar way between these two microorganisms ( Chaturongakul and Boor, 2004 , 2006 ; Cosgrave, 2010 ; Shin et al, 2010a ; Utratna et al, 2014 ; O’Donoghue,, 2016 ; Guerreiro et al, 2020 ; Hsu et al, 2020 ).…”
Section: Signal Transductionmentioning
confidence: 97%